2008
DOI: 10.1109/tdei.2008.4591223
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental insulation characteristics of high-pressure CO<sub>2</sub> gas for gas-insulated power equipment - effect of coating conductor on insulation performance and effect of decomposition products on creeping insulation of spacer -

Abstract: Currently, environmental problems such as global warming are important issues, and SF 6 has been identified as a greenhouse gas with a long atmospheric lifetime. Therefore, in the long term, it is preferable to reduce the amount of SF 6 used as an insulating gas. It is thus important to discuss the possibility of using more environmentally friendly gases as alternative insulation for gas-insulated apparatus. In this paper, we describe the fundamental insulation breakdown characteristics of high-pressure CO 2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…This study [38] also suggested that the dew point of moisture in SF 6 gas was less than -10 °C for the surface insulation performance and that the maintenance level of moisture decreased with gas pressure. Moreover, the insulation resistance of a spacer decreased because of the absorption of moisture in air [39]. These results suggest that the candidate gases require a low moisture content to ensure the surface insulation performance and to preserve the insulation resistance of a spacer.…”
Section: Insulation Reliabilitymentioning
confidence: 94%
See 1 more Smart Citation
“…This study [38] also suggested that the dew point of moisture in SF 6 gas was less than -10 °C for the surface insulation performance and that the maintenance level of moisture decreased with gas pressure. Moreover, the insulation resistance of a spacer decreased because of the absorption of moisture in air [39]. These results suggest that the candidate gases require a low moisture content to ensure the surface insulation performance and to preserve the insulation resistance of a spacer.…”
Section: Insulation Reliabilitymentioning
confidence: 94%
“…Nitta et al [38] and Goshima et al [39] presented the aforementioned mechanism on the degradation of surface insulation performance and the decreasing insulation resistance of a spacer because of moisture in the insulation gas respectively. However, this mechanism was investigated on the flashover characteristics on moisture content and temperature variations in SF 6 .…”
Section: Insulation Reliabilitymentioning
confidence: 99%
“…In addition to selecting the insulating gas, engineering techniques can be applied to an insulation design method, and these techniques should be integrated into high-voltage apparatus with a selection method of insulating gas that considers the electron swarm parameters. The engineering techniques are improvements in electrodes and solid dielectrics, details of which can be found in references [11,[32][33][34][35][36]. The theoretical principles governing the engineering techniques are the suppression of electron generation and relaxation of the concentrated electric field.…”
Section: Insulation Design Methods Of An Insulating Gas Alternative Tomentioning
confidence: 99%
“…Their dielectric strength and characteristics have been compared with those of SF 6 [9]. In addition to gas insulation, composite insulation has been applied to SF 6 -free gas-insulated switchgear (GIS), instead of simple dielectric insulations by vacuum, gases, or solid dielectrics [10,11]. Composite insulation is a method of using a solid dielectric and an insulating gas together.…”
Section: Introductionmentioning
confidence: 99%
“…The SF 6 alternative gases consist of conventional gases (N 2 , CO 2 , air, etc.) [7]- [9], CF 3 I gas [10], PFC gases (c-C 4 F 8 , etc.) [11], perfluoroketone gases (C 5 F 10 O) [12], perfluoronitrile gases (C 4 F 7 N) [13], refrigerant gases (HFO-1234ze and R-134a) [14], [15], and so on [16], [17].…”
Section: Introductionmentioning
confidence: 99%